Build the ultimate home theater PC - Tittel, Ed (Wiley Technology Pub., 2006)
The best of both worlds-now THIS is entertainment. You love tinkering with technology. The digital lifestyle is your lifestyle. So building your own Home Theater PC just might be as entertaining as using it. In these pages, a couple of fellow tinkerers explain the components and subsystems of a Home Theater PC and help you choose and pur- chase parts, assemble and test the PC, install Windows(r) Media Center Edition, and get the whole thing up and running. Then, invite your friends over and watch 'em turn green.